Innovative approaches in axial spondyloarthritis: exploring emerging trends in treatment and management - Rogowska, Jagoda; Balińska, Wiktoria; Wąsik, Jakub; Marek, Aleksandra (Journal of Medical Science, 2025)
Background. Axial Spondyloarthritis (axSpA) is a chronic inflammatory disease affecting the axial skeleton, resulting in chronic pain, reduced mobility, and potential spinal fusion. Traditional therapies emphasise symptomatic control via nonsteroidal anti-inflammatory drugs (NSAIDs) and physical therapy. Recent advances, however, including biologic agents and JAK inhibitors, have opened new therapeutic possibilities.Material and methods. A comprehensive literature review was conducted using databases such as PubMed and Scopus. The literature search included English-language publications between January 2018 and February 2024. We included clinical trials, meta-analyses, systematic reviews, cohort studies, and significant basic science studies. Publications outside these criteria or those in other languages were excluded. Methodological rigour and limitations of included studies were critically discussed.Results. Key recent advances include biologic therapies targeting IL-17 and IL-23 cytokine pathways, demonstrating significant efficacy in controlling inflammation and improving function. Additionally, precision medicine, microbiome-based interventions, and advanced imaging techniques enhance personalised treatment strategies.Conclusions. Integrating novel pharmacological approaches with lifestyle modifications presents a promising strategy for optimising axSpA management. Long-term studies are required to assess the full impact of these innovations on disease progression.